A study on inverted Tshaped micro strip antenna at different frequencies (International Journal of Engineering and Computer Science, 2013)
This is the era of communication, where any information can be globalised in very short time around the world. Today we are having a lot of advanced technology where any information can be convey in just a click and this all things are possible due to compact size of the devices, and microstrip patch antenna play a very important role to reduce the size of communicating devices. In this paper we are study about the bandwidth and return loss at frequency 4GHz, 5GHz and 6GHz. In here we are taking a inverted T shaped [1] patch and find the results at different frequency but the important point on this paper is,the feed point location is approximately is same for each frequency.